Cost-effectiveness of brentuximab vedotin plus chemotherapy as frontline treatment of stage IV Hodgkin lymphoma in Italy - Chiara Bini; Andrea Marcellusi; Francesco Saverio Mennini; Silvia Ripoli; Laura Fioravanti; Victoria Federico Paly; Alexa Molinari; Paolo Morelli; Stanimira Krotneva; Shujun Li (Global & Regional Health Technology Assessment, 2024)
Objectives: Advanced Hodgkin’s lymphoma (HL) is a rare severe neoplasm, significantly limiting the ability of patients to do daily activities among other impacts of the cancer. Many adult patients present with advanced stage disease (stages III/IV). This analysis investigates the cost-effectiveness of brentuximab vedotin (BV) in combination with doxorubicin, vinblastine, and dacarbarzine (AVD) versus ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) for the frontline treatment of stage IV HL in Italy based on data from the ECHELON-1 clinical trial.